Transkulturelle Kompetenz und Selbstempathie - Ortloff, Elisabeth (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2016)
The present bachelor thesis gives an insight into the concept of transculturation by Wolfgang Welsch. Given Welsch's findings, a model of transcultural competence is developed and proposed which largely is based on the 3-pillar-model of transcultural competence by Dagmar Domenig and the model of competencies for the Global Development Education by the Federal Ministry for Economic Cooperation and Development. Three pillars form the new model proposed here, namely knowledge of corroboration (cognition), self-reflection (rate) and empathy (action). Based on the action-oriented communication model of Nonviolent Communication by Marshall B. Rosenberg, the importance of self-empathy is shown in relation to the three mentioned pillars. The aim of this work is - in addition to developing a competence model - to discuss how self-empathy is a necessary condition for promoting transcultural competence.

Die vorliegende Bachelorarbeit gibt einen Einblick in das Konzept der Transkulturalität nach Wolfgang Welsch. Angesichts der Erkenntnisse Welschs wird ein Modell für transkulturelle Kompetenz entwickelt und vorgeschlagen, welches sich maßgeblich an dem 3-Säulen-Modell transkultureller Kompetenz nach Dagmar Domenig sowie dem Kompetenzmodell für den Lernbereich Globale Entwicklung des Bundesministeriums für wirtschaftliche Zusammenarbeit und Entwicklung (BMZ) orientiert. Orientierungswissen (Erkennen), Selbstreflexion (Bewerten) und Empathie (Handeln) bilden die drei Säulen des hier neu vorgeschlagenen Konzeptes. Ausgehend von dem handlungs-orientierten Kommunikationsprinzip der Gewaltfreien Kommunikation nach Marshall B. Rosenberg soll die Bedeutung der Selbstempathie in Bezug auf die drei genannten Säulen dargestellt werden. Ziel der Arbeit ist es daher - neben der Entwicklung des Kompetenzmodells - zu diskutieren, inwiefern Selbstempathie notwendige Voraussetzung für die Förderung transkultureller Kompetenz ist.
Transcultural Competence and Self-Empathy: Proposal for a model of transcultural competence considering self-em-pathy following the concept of Nonviolent Communication
Vorschlag für ein Modell transkultureller Kompetenz unter Berücksichtigung von Selbstempathie nach dem Prinzip der Gewaltfreien Kommunikation
Keywords: Interkulturalität; Selbstliebe; Kulturelle Kompetenz; 300 Sozialwissenschaften